First Report on Purpureocillium lilacinum Infection of Indoor-Cultivated Morel Primordia - Segula Masaphy (Agriculture, 2022)
The cultivation of morel mushrooms (Morchella spp.) outdoors or in controlled indoor systems is a relatively new practice, and infections are beginning to be observed. Infection of indoor-cultivated Morchella rufobrunnea initials (primordia) occurred at our research facilities in Israel. The mushroom initials turned brown, were covered with a dense white mycelium of a foreign fungus and were disintegrated soon after. The isolation of a fungal contaminant from the infected mushroom revealed small colonies with a pinkish spore zone on potato dextrose agar medium. Molecular identification using partial large subunit 28S ribosomal DNA and rRNA internal transcribed spacer sequences identified the fungus as Purpureocillium lilacinum. Inoculation of Morchella colony on agar plat with the isolated fungus caused browning and inhibition of mycelial growth. Inoculation of a healthy primordium with P. lilacinum spores resulted in its browning and deterioration. This is the first report of an infection of indoor-cultivated mushroom and the first showing P. lilacinum as a pathogen of morels.